Odpowiedź :
Odpowiedź:
a)
2^-2/3^-3 * (4/9)² = 27/4 * 16/81 = 4/3 = 1 1/3
b)
[(2/3)^-2]^-2 = [(3/2)²]^-2 = (9/4)^-2 = (4/9)² = 16/81
c)
(6^0 + 0^6)/6^-1 + (4^6 - 16³) = 1/6^-1 + [(4^6 - (4²)³] = 6 + (4^6 - 4^6) = 6 +0 = 6
d)
[(1/3)^4 * (2/3)^-5] : 6^-2 = [(1/3)^4 * (2/3)^5] * 6² = 2/3(1/3 * 2/3)^4 * 36 =
= 2/3 * 36(2/9)^4 = 1/3 * 18 = 6
e)
(0,5 * 8^6 - 2 * 16^4) : 7³ = [0,5 * (2³)^6 - 2 * (2^4)^4] : 7³ =
= (1/2 * 2^18 - 2 * 2^16) : 7³ = (2^-1 * 2^18 - 2^17) : 7³ = (2^17 - 2^17) : 7³ =
= 0 * 7³ = 0
f)
[(5/2)³ : (2/5)²] * (5/2)^-4 = 5/2(5/2 * 2/5)² * (2/5)^4 = 5/2 * (2/5)^4 = (2/5)³ = 8/125
Szczegółowe wyjaśnienie: